Interest-in-schooling among secondary school students: a regression analysis of social media, school climate and intrinsic motivation (2019)
It has been observed that interest-in-schooling is an important factor associated with the learning process. However, it was observed that a negative attitude towards schooling has resulted in indiscipline, low academic achievement, absenteeism and dropout among secondary school students in Nigeria. This makes it imperative to examine the influencing factors (social media. school climate and intrinsic motivation) on interest-in-schooling among secondary school students. The study adopted the descriptive research design of the correlational type. A total of three hundred (300) secondary school students were used. Ten (10) schools in Badagry Local Government Area in Lagos State were selected using simple random sampling. Three research hypotheses were generated and tested at 0.05 level of significance. Reliable instruments (Interest-in-schooling Scale; a =0.83, Social Media Usage Scale. a =0.87, School Climate Scale; a = 0.85, Intrinsic Motivation Scale; a =0.72) were used in collecting the data. Data collected was analyzed using Pearson Product Moment Correlation and Multiple Regression Statistical Tools. It was discovered that there was significant relationship between school climate (r = 0.703), social media usage (r = - 0.210), intrinsic motivation (r = 0.453) and interest-in-schooling. Regression analysis revealed that the three independent variables (school climate, social media usage and intrinsic motivation) combined accounted for 54.5% (Adj. R: = .545) Variation in the prediction of interest-in-schooling. The strongest predictors of interest-in-schooling were school climate and social media usage, followed by intrinsic motivation. It was recommended that parents, school counsellors and rehabilitation officers working with students who lack interest- in-schooling should take cognizance of the influence of social media usage, school climate and intrinsic motivation in helping them develop their interest-in-schooling.